Can charge scheduling incentives mitigate the impact of EVs on the power grid? - Ahmed Ali A. Mohamed; Stephanie Lojano; Carlos Maldonado; Tamer Ibrahim; Hebatallah E. Mostafa; Razib Sarkar; Tafadar Soujad; Hegazy Rezk; Mujahed AlDhaifallah (Energy Reports, 2023)
The number of Electric Vehicles (EVs) on the roads is expected to dramatically rise within the next few years. This is poised to substantially increase the total electricity demand due to EV charging. The key question is whether today’s distributions systems can handle this increased charging demand. Our central hypothesis is that coordinated charging is a must to enable wide scale deployment of EV chargers. Coordinated charging refers to scheduling, and possibly optimizing, the charging action of EVs so that charging is more focused during grid off-peak hours. Due to the importance of charging incentives, the objective of this paper is to take a step back and obtain real data that help gauge EV drivers’ level of acceptance to charging scheduling incentives. Using New York City as a living lab, a case study was carried out to analyze the effectiveness of those incentives. The results of a survey, taken by 119 New Yorkers, shed light on people’s response to charging incentives. For instance, 85% of the survey respondents chose to travel longer for a cheaper EVSE instead of heading to a near EVSE at a higher cost.